Medical Student Syndrome in Medical University students in Jordan: A Cross-sectional Study - AlSamhori, Jehad Feras; AlSamhori, Abdel Rahman Feras; AlSamhori, Ahmad Feras; Rihani, Jude; Shaban, Leen; Omeish, Rana (International Journal of Medical Students, 2023)
BACKGROUND: The widely recognized phenomenon known as 'medical student syndrome' refers to the tendency of many medical students to develop fears and symptoms of illnesses they are studying. Extensive research has underscored the substantial psychological pressure that medical students endure due to factors like a demanding workload, exam-related stress, anxiety arising from new clinical experiences, and the competitive academic environment. Given its classification as a mental health issue, 'medical student syndrome' has been investigated in multiple countries. Consequently, our study aims to delve deeper into this phenomenon among medical students, considering various demographic factors. METHODS: A cross-sectional study was conducted. The survey includes sociodemographic questions and attitudes toward the syndrome, adapted from a Polish study. Data was using SPSS, with statistical tests conducted at a 95% confidence level. RESULTS: A total of 1,050 participants completed the questionnaire for this study, with 67.3% being females. The average age was 20.91 years, and the majority were unmarried (98.2%). Most participants reported a monthly income of less than 500 JDs, and only 16.2% identified as smokers. Clinical students accounted for 33.6% of the sample, while 11.2% indicated a history of mental illnesses. Additionally, 36.3% had taken previous courses related to mental illnesses, and 13.7% had sought psychiatric consultation. Furthermore, 15.6% had utilized psychiatric or psychotherapeutic counseling for other reasons, and 26.6% expressed a desire to visit a psychiatrist or psychologist due to their fear of falling ill. Mann–Whitney U and Kruskal–Wallis tests were conducted to explore potential differences in total scores based on demographic and mental background factors. Preclinical students had significantly higher mean scores compared to clinical students (41.68 vs. 39.35, p = 0.001). Respondents who had used psychiatric or psychotherapeutic counseling for reasons other than those inquired had significantly higher scores than those who did not (43.85 vs. 40.35, p < 0.001). Similarly, respondents planning to visit a psychiatrist/psychologist due to their fear of falling ill scored significantly higher than those who did not share this intention (43.85 vs. 39.96, p < 0.001). Multiple linear regression analysis revealed that the "year of study" variable was the only significant predictor of the total score, with a coefficient of -3.196, a t-statistic of -4.057, and a p-value < 0.001. This negative coefficient suggested that as the year of study increased, the total score tended to decrease significantly. However, the model had relatively weak explanatory power, with R² indicating that it explained only about 3.5% of the variance in the dependent variable, and R²adj accounting for approximately 2.7% after adjusting for model complexity. CONCLUSION: In summary, the study included a diverse group of participants with varying demographic and mental background factors. Preclinical students tended to have higher scores, and those with a history of seeking mental health services or expressing an intention to do so had higher scores. The year of study was a significant predictor of the total score, suggesting that as students progressed in their studies, their scores tended to decrease. However, the model's overall explanatory power was relatively limited.